Anthesis and flower visitors in Curculigo latifolia dryand - Ismail, Mohd Firdaus; Abdullah, Nur Ashikin Psyquay; Saleh, Ghizan; Ismail, Maznah (Academy Journals Inc., 2010)
The chronology of flower anthesis in Curculigo latifolia Dryand was studied. This was to described the flowering timeline and to observed flower visitors. Observation on adult plants were carried out from 0500 until 2000 hours and repeated twice. The most common visitors were black ants found nesting between the leaf and bees. Visitation by bees mainly occurred in the morning between 0930 and 1000 hours. Anthesis begun at 0630 and flowers were fully expanded at 0930 exposing dehisced anthers and glistening stigma. Flowers lasted for a day and completely withered by 2000 hours.